2016
DOI: 10.4103/0976-7800.179167
|View full text |Cite
|
Sign up to set email alerts
|

Giant mucinous cystadenocarcinoma of ovary: A case report and review of literature

Abstract: Giant cystadenocarcinomas of the ovary are rarely described. Huge ovarian masses are mostly benign, but malignancy should be ruled out by investigations and clinical assessment. Giant cysts require resection because of compressive symptoms or risk of malignancy and their management invariably requires laparotomy to prevent perforation and spillage of the cyst fluid into peritoneal cavity. Here, we present a case of a 42-year-old female with severe and rapidly growing abdominal distension operated for explorato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 2 publications
0
31
0
Order By: Relevance
“…This case emphasises that while operating on such huge tumour care has to be taken to manage these complications as well as the problems associated with sudden decompression [7]. Our case also emphasises that management of ovarian cyst depends on the patients age, the size of the cyst and its histopathological nature for large ovarian masses with a risk of malignancy we suggest laparotomy and intraoperative frozen section.…”
Section: Resultsmentioning
confidence: 99%
“…This case emphasises that while operating on such huge tumour care has to be taken to manage these complications as well as the problems associated with sudden decompression [7]. Our case also emphasises that management of ovarian cyst depends on the patients age, the size of the cyst and its histopathological nature for large ovarian masses with a risk of malignancy we suggest laparotomy and intraoperative frozen section.…”
Section: Resultsmentioning
confidence: 99%
“…Giant ovarian cysts constitute a challenging condition in general practice because of their nonspecific clinical features and findings from physical examination resulting to a wide range of differential diagnoses [ 10 ]. These differential diagnoses include pelvic endometriosis, intra-abdominal pregnancy, intra-abdominal cysts from varying origins (omentum, ovary, kidney, liver, pancreas, cystic lymphangiomas, choledochal cysts), hydronephrosis and accentuated obesity [ 5 , 10 ]. Despite being asymptomatic, GOCs can cause serious complications like torsion, suppuration, obstruction, and perforation necessitating urgent admission [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our patient assumed the increasing abdominal gait was due to obesity which was not a call for concern and she sought medical attention after it persisted for years. Lack of diagnostic facilities in primary settings in SSA also contributes to late diagnosis [ 10 ]. Although US scans are relatively common in recent practice, it is apparently not used in many centres in SSA partly because of the lack of the expertise to manage them or their absence in these centres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The list of cystic masses of the abdominal cavity is long (Table 1). Size is a major determinant of the clinical diagnosis of such masses; although most adnexal cystic masses are benign, the possibility of malignancy mandates the need for accurate diagnosis and treatment [1,2]. Most authors have suggested that adnexal cysts that are unilocular, unilateral and less than 5 cm are benign [3].…”
Section: Case Report Discussionmentioning
confidence: 99%